Dietary L-Cysteine Improves the Antioxidative Potential and Lipid Metabolism in Rats Fed a Normal Diet - LEE, Seulki; HAN, Kyu-Ho; NAKAMURA, Yumi; KAWAKAMI, Sakura; SHIMADA, Ken-ichiro; HAYAKAWA, Touru; ONOUE, Hirotake; FUKUSHIMA, Michihiro (Bioscience, biotechnology, and biochemistry, 2013)
L-Cysteine works as a precursor of the antioxidant, glutathione. We investigated the effects of L-cysteine (1% and 2%) on lipid metabolism and the antioxidative system in rats fed a normal diet. Administering L-cysteine dependently decreased the food intake, fat mass weight and body weight dose. Dietary L-cysteine also decreased the triglyceride levels in the serum and liver. However, there were no significant differences in the hepatic TBARS and glutathione (GSH) levels among the groups. The activities of catalase and glutathione reductase in the rats receiving 2% L-cysteine were significantly higher (p<0.05) than in the control rats. These results suggest that dietary L-cysteine dose-dependently affected the antioxidative enzyme activities, and the lipid levels in the serum and liver which might be related to the reduced food intake.